Pengaruh Pajak Daerah dan Retribusi Daerah Terhadap Kemandirian Keuangan Daerah Pada Pemerintah Kabupaten/Kota Provinsi Sumatera Selatan - Adelina, Chairani; Betriana, Meirani (Politeknik Raflesia Press, 2024)
This research aims to determine the effect of regional taxes and regional levies on the financial independence of regional governments in South Sumatra Province. This research uses a quantitative approach and quantitative data types with secondary data sources obtained from the LKPD of the Regional Government of South Sumatra Province for 2020 - 2022. The data was processed using the SPSS application and analyzed using multiple linear regression analysis. The results of this research show that regional taxes have an influence on regional financial independence with a significance value of 0.00 < 0.05, while regional levies do not have a significant influence on regional financial independence with a value of 0.176 > 0.05. However, regional taxes and regional levies simultaneously influence regional financial independence with a significance value of 0.00 < 0.05 and with a coefficient of determination of 0.899.